TRANSFORMATIONAL LEADERSHIP OF SCHOOL ADMINISTRATORS THAT AFFECT COMMUNITY INVOLVEMENT OF SMALL SCHOOL IN NAKHON SI THAMMARAT PRIMARY EDUCATIONAL SERVICE AREA OFFICE 1 - Yiamkorn, Jutamas; Thammatikul, Akkara; Chatakan, Werayut (Journal of MCU Nakhondhat, 2023)
The purposes of this research were to study 1) The Transformational leadership of administrators in small schools 2) Community participation in small schools 3) The Transformational Leadership of administrators affecting of community participation in small schools 4) Community participation in small schools affecting community participation in small educational institutions Nakhon Si Thammarat Primary Educational Service Area Office 1. Is a quantitative research. The research samples included 217 teachers The results of the research revealed that 1) The Transformational leadership of school administrators The overall picture is at the highest level. 2) Community participation in small educational institutions. 3) The Transformational leadership of school administrators affecting community participation in small educational institutions found that Transformational leadership of school administrators was at a high level. All 4 aspects are aspects of inspiration. individual consideration leadership change and leadership have a positive effect on community participation in small educational Nakhon Si Thammarat Primary Educational Service Area Office 1 had a high positive relationship (r = .73**) there were statistical significant relationship at 0.01. 4) The role of a Transformational leadership affecting community participation in small educational institutions, it was found that a good school administrator must be a Transformational leaders. To be a catalyst for community cooperation Because the community wants to see the development of schools in the community. Ready and willing to cooperate in promoting and participating in various developments. Transformational leadership for good results in the organization from all departments to trust, trust, and cooperate to drive higher quality educational institutes.